2019
DOI: 10.1148/radiol.2018181286
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Noncalcium Dual-Energy CT: Detection of Lumbar Disk Herniation in Comparison with Standard Gray-scale CT

Abstract: To assess the diagnostic performance of dual-energy CT with reconstruction of virtual noncalcium (VNCa) images for the detection of lumbar disk herniation compared with standard CT image reconstruction. Materials and Methods:For this retrospective study, 41 patients (243 intervertebral disks; overall mean age, 68 years; 24 women [mean age, 68 years] and 17 men [mean age, 68 years]) underwent clinically indicated third-generation, dual-source, dual-energy CT and 3.0-T MRI within 2 weeks between March 2017 and J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(56 citation statements)
references
References 29 publications
1
55
0
Order By: Relevance
“…A previous study by Booz et al showed higher sensitivity and specificity of DECT compared with standard CT in detecting lumbar disk herniation and spinal nerve root impingement, suggesting that DECT might be as accurate as MRI [ 8 ]. However, Booz et al used a different reconstruction algorithm (virtual non-calcium reconstruction), while we investigated a three-material decomposition algorithm with a collagen-specific gradient.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study by Booz et al showed higher sensitivity and specificity of DECT compared with standard CT in detecting lumbar disk herniation and spinal nerve root impingement, suggesting that DECT might be as accurate as MRI [ 8 ]. However, Booz et al used a different reconstruction algorithm (virtual non-calcium reconstruction), while we investigated a three-material decomposition algorithm with a collagen-specific gradient.…”
Section: Discussionmentioning
confidence: 99%
“…In patients who have contraindications to diagnostic MRI or need a timely CT scan for other indications, disk visualization by CT could be helpful as an alternative diagnostic instrument. Previous studies have highlighted the value of DECT in intervertebral disk evaluation and have shown a higher sensitivity and specificity of DECT compared with standard CT in detecting lumbar disk herniation and spinal nerve root impingement [ 8 , 9 ]. However, these studies used different DECT reconstruction algorithms and did not compare results with MRI—the current diagnostic standard in detecting disk pathology.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to detecting marrow edema, VNCa color map overlay images have been found to have higher overall sensitivity and specificity (91% and 92%, respectively) than standard CT for detecting lumbar disk herniation, using MRI as a reference standard 82 (Figure 6). In patients with vertebral fractures, color overlay collagen maps created using three-material decomposition techniques were found to be both sensitive (0.85) and specific (0.75) for disk injuries, with sensitivity varying from 0.80 to 0.98 depending on severity of disk injury.…”
Section: Spine and Dentalmentioning
confidence: 99%
“…77 Additional studies published after this meta-analysis assessing edema in vertebral compression fractures with VNCa demonstrated very similar sensitivities (between 85% and 98%) and specificities (between 92% and 99%), with an area under the receiver-operating characteristic curve ranging from 0.88 to 0.97. [78][79][80][81] In addition to detecting marrow edema, VNCa color map overlay images have been found to have higher overall sensitivity and specificity (91% and 92%, respectively) than standard CT for detecting lumbar disk herniation, using MRI as a reference standard 82 (Figure 6). In patients with vertebral fractures, color overlay collagen maps created using three-material decomposition techniques were found to be both sensitive (0.85) and specific (0.75) for disk injuries, with sensitivity varying from 0.80 to 0.98 depending on severity of disk injury.…”
Section: Bone Marrow and Disk Assessmentmentioning
confidence: 99%
“…Recent studies suggest that DECT is also useful in depicting the morphology and microstructural changes of IVDs [17,18]. Additionally, virtual non-calcium (VnCa) maps have been shown to increase diagnostic performance and confidence for depicting lumbar disc herniation as compared with standard CT [19]. However, a systematic analysis of quantitative and qualitative aspects has yet to be conducted.…”
Section: Introductionmentioning
confidence: 99%